Co-treatment of Waste From Steelmaking Processes: Steel Slag-Based Carbon Capture and Storage by Mineralization - Zhao, Qing; Chu, Xinyi; Mei, Xiaohui; Meng, Qingzhang; Li, Jingyu; Liu, Chengjun; Saxén, Henrik; Zevenhoven, Ron (Frontiers in Chemistry, 2020)
The iron and steel industry is an energy-intensive sector, and large amounts of waste/ by-products are generated during the steelmaking process, such as CO2, metallurgical slag, and wastewater. Enhancing the development and deployment of treating waste from the steelmaking process will be environment friendly and resource-saving. Capturing CO2 by steel slag (SS) via mineralization is regarded to be an excellent choice due to the high basicity of the slag. In this paper, recent research on the steel slag-based carbon capture and storage (SS-CCS) by mineralization was summarized. Three routes of SS-CCS are compared including, direct gas-solid carbonation, direct aqueous carbonation, and indirect carbonation, respectively. Furthermore, the challenges and prospects for further development of the SS-CCS were discussed.